Effect of surfactant on degradation of Aspergillus sp. and Trichoderma sp. mediated crude oil. Issue 7 (28th May 2023) - Khandelwal, Ashish; Singh, Shashi Bala; Sharma, Anamika; Nain, Lata; Varghese, Eldho; Singh, Neera
ABSTRACT: Three fungal strains isolated from the oily sludge contaminated soil were identified as Trichoderma atroviride, Aspergillus nidulans and Aspergillus sydowii using 18s rDNA sequences and BLAST analysis. Degradation of crude oil was studied using the isolated fungi, without (–T) and with (+T) Tween-80. The total percent degradation of aliphatic hydrocarbon in crude oil (4460.1 mg kg −1 ) was in the range of 66.9–83.5% (–T) and 63.4–84.7 (+T) after 30 days incubation. However, the gravimetric study showed that total petroleum hydrocarbon degraded in the range of 27.7–36.8% (–T) and 31.5–45.5% (+T) after 30 days. Cluster dendrogram, based on Euclidean distance, deduced grouped hydrocarbons into four clusters depending on their percent degradation. A comparison of the regression coefficient of principal component, PC1, suggested that the degradation of aliphatic hydrocarbons was fast during initial days (15 days) as compared to 30 days. The study suggested that fungi isolated from the oil sludge contaminated soil, especially T. atroviride and A. sydowii, have potential to degrade aliphatic hydrocarbons/crude oil in the environmental matrix.